Analisis Wacana Kritis Film Pendek Ngapak Tegal "Mardiyah" (Sutasoma : Jurnal Sastra Jawa, 2022)
The short film ngapak Mardiyah from the Tegal area produced by Mr. Hidayah from the Hidayah Official youtube channel, according to the cultural and linguistic aspects. The researcher took this film as the object of research because it fits the title Mardiyah, but there is no female figure named Mardiyah, which might make the audience wonder why Mardiyah is not shown. The existence of these problems, the researchers analyzed using Teun A. Van Dijk's discourse analysis which focused on three dimensions: text structure, social cognition, and social context. This approach uses descriptive qualitative discourse analysis with data collection techniques document study and literature study. This study uses content analysis techniques to determine the content of a message, the results of the first study, the structure of the text found that there are four scenes that were analyzed based on the macro structure, superstructure and micro structure. Second, on social cognition based on the awareness of the short film maker Mardiyah regarding her ideas, there are three elements, namely elements of knowledge, opinions and attitudes, ideology. Third, in the social context, it is found that the problems that arise in the short film ngapak Mardiyah are not only social disparities, but the figure of Mardiyah as a parable to express one's frustration. Keywords: film analysis; language; culture